A positive feedback loop between two C-type lectins originated from gene duplication and relish promotes the expression of antimicrobial peptides in Procambarus clarkii - Dai, Xiaoling; Sun, Mengling; Nie, Ximei; Zhao, Yuqi; Xu, Hao; Han, Zhengxiao; Gao, Tianheng; Huang, Xin; Ren, Qian (Frontiers in Immunology, 2022)
Gene duplication (GD) leads to the expansion of gene families that contributes organisms adapting to stress or environment and dealing with the infection of various pathogens. C-type lectins (CTLs) in crustaceans undergo gene expansion and participate in various immune responses. However, the functions of different CTL produced by GD are not fully characterized. In the present study, two CTL genes (designated as PcLec-EPS and PcLec-QPS, respectively) were identified from Procambarus clarkii. PcLec-EPS and PcLec-QPS originate from GD and the main difference between them is exon 3. PcLec-EPS and PcLec-QPS respectively contains EPS and QPS motif in their carbohydrate recognition domain. The mRNA levels of PcLec-EPS and PcLec-QPS in hemocytes, gills, intestine and lymph underwent time-dependent enhancement after D-Mannose and D-Galactose challenge. Recombinant PcLec-EPS and PcLec-QPS could bind to carbohydrates and microbes, and agglutinate bacteria. The results of experiments on recombinant protein injection and RNA interference indicate that PcLec-EPS and PcLec-QPS can respectively strong recognize and bind D-Mannose and D-Galactose, activate the Relish transcriptional factor, and further upregulate the expression of different antimicrobial peptides (AMPs). In addition, these two CTLs and Relish could positively regulate the expression of each other, suggesting that there is a positive feedback loop between two CTLs and Relish that regulates the expression of AMPs. It may contribute to the expansion of the immune response for host quickly and efficiently eliminating pathogenic microorganisms. This study provides new knowledge for clear understanding the significance and function of different CTL generated by GD in immune defenses in crustacean.